Relationship of depersonalization and suicidality in depressed patients - Tošić-Golubović Suzana; Žikić Olivera; Slavković Violeta; Nikolić Gordana; Simonović Maja (Vojnosanitetski Pregled)
Background/Aim. Depersonalization is considered to be the third leading symptom in psychiatric morbidity. The aim of this study was to investigate the correlation of depersonalization and different patterns of suicidal behaviour in patients suffering from depresssive disorder. Methods. The study included 119 depressed patients divided into two groups: the first group consisted of depressed patients with clinically manifested depersonalization according to the Cambridge Depresonalisation Scale presented score ≥ 70, and the second group consisted of the patients whithout clinically manifested depersonalization symptomatology, or, it was on the subsyndromal level. Subsequently, these two groups were compared regarding the suicidality indicators. Results. According to the Scale for Suicide Ideation of Beck, the depressed patients with depersonalization had statistically significantly higher scores regarding suicidal ideation, both active and passive, more often manifested suicidal desire, suicidal planning and overall suicidality (p < 0.000). Positive ideation, as a protective factor, was reduced in this group (p < 0.000). These patients had more previous suicide attempts (p < 0.001) and family history of suicides (p = 0.004). The depressed patients with depersonalization had 8 times more often active suicidal desire, 11 times more often passive suicidal desire and 5 times more often suicidal planning compared to patients without depersonalization. Conclusion. Suicidal potential, manifested in various patterns of suicidal behaviour among the patients suffering from depressive disorder with clinically manifested depersonalization is prominent. It is necessary to pay particular attention to depersonalization level during diagnostic and treatment procedure of the depressed patients having in mind that it may be associated with high suicidal potential.